SKORING CORONARY ARTERY CALSIUM PADA INDIVIDU USIA DEWASA AKHIR DAN LANSIA DENGAN HIPERTENSI - Putu Suryabrata Adnyana; Machrumnizar Machrumnizar (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2023)
Hypertension causes an increase in coronary artery calcium (CAC), which is a strong predictor of new-onset hypertension and occurrences related to atherosclerotic cardiovascular disease in people either with or without hypertension. The medical application of CAC scoring to adjust hypertension management has received slight attention and is poorly defined. In Indonesia, research on the benefits of CAC assessment for hypertension is yet very limited. This study will show the association of hypertension with CAC rating, age, and gender. This cross-sectional study used secondary data in the form of medical records from 163 patients (88 men, 75 women; range 40-70 years) at Siloam Hospital TB Simatupang. Sample collection was carried out using consecutive nonrandom sampling. Only medical records with complete physical examination results and CAC scoring will be further analyzed. The Mann-Whitney statistical test was carried out using the SPSS 25.0 program to see the relationship between CAC scoring and hypertension, with a value of p=0.002 and a significance level of p<0.05. To assess the relationship between age and gender with the incidence of hypertension, a chi square test was carried out, with each value p = 0.011 and p = 0.141 (p <0.05). The results showed a relationship between CAC scoring and hypertension in late adulthood and elderly individuals.